Improving Physics Concepts and Students’ Learning Interests Through Interactive Learning Media - Rohmah, Inayatur; Maftukhin, Arif; Kurniawan, Eko Setyadi (Radiasi : Jurnal Berkala Pendidikan Fisika, 2025)
This study aims to determine the effectiveness of interactive multimedia-assisted learning media in improving concept understanding and students’ learning interests and determine students’ responses to interactive multimedia learning media. The research method using Pre-test Post-test Control Group Design. The data collection techniques used were observation, tests, and questionnaires. The subjects of this study were students of class X SMA Negeri 1 Petanahan with a limited trial of 10 students, an experimental class of 36 students, and a control of 36 students. The data obtained were analyzed using the n-gain formula with n-gain criteria. The result of this study indicate the effectiveness of interactive multimedia learning media on concept understanding and learning interest seen from the results of pretest posttest concept understanding and pre post learning interest. The result of data analysis showed that the understanding of concept and interest in learning in the experimental class both overall and in each indicator experienced a better increase than in the control class. The result of the n-gain value of increasing concept understanding is 0.69 with a moderate category and the result of the n-gain value of increasing interest in learning is 0.69 with a moderate category. Thus it can be concluded that the interactive multimedia learning media developed can effectively improve learning interest.